Exceptional Superionic Conductivity in Disordered Sodium Decahydro‐closo‐decaborate. (13th October 2014) - Udovic, Terrence J.; Matsuo, Motoaki; Tang, Wan Si; Wu, Hui; Stavila, Vitalie; Soloninin, Alexei V.; Skoryunov, Roman V.; Babanova, Olga A.; Skripov, Alexander V.; Rush, John J.; Unemoto, Atsushi; Takamura, Hitoshi; et al.
<x xml:space="preserve">Abstract</x> Na2B10H10 exhibits exceptional superionic conductivity above ca. 360 K (e.g., ca. 0.01 S cm−1 at 383 K) concomitant with its transition from an ordered monoclinic structure to a face‐centered‐cubic arrangement of orientationally disordered B10H102− anions harboring a vacancy‐rich Na+ cation sublattice. This discovery represents a major advancement for solid‐state Na+ fast‐ion conduction at technologically relevant device temperatures. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>